Psychosocial dynamics of therapy and rehabilitation results in hospital conditions - Łukasiak, Adam; Komasiński, Marek; Czernicki, Jan (European Journal of Clinical and Experimental Medicine, 2005)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: center; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">In this thesis authors presents course of hospital patients psychosocial reactions, which are specific reply on disease or disability. At the same time authors presents and discuss basie advantage and disadvantage of therapy and rehabilitation in hospital conditions.